Implementasi Media Aplikasi Moodle Dalam Pembelajaran Virtual Berbasis Kelas Melalui Sistem Pembelajaran Online Terpadu (SIDU) di SMA Islam Al Azhar 19 Ciracas Jakarta Timur - Yusron, M Alhabib; Siskandar, Siskandar; Shunhaji, Akhmad (El-Idare, 2023)
This study aims to analyze and evaluate the implementation of the Moodle application in classroom-based virtual learning through the Integrated Online Learning System (SIDU and its implications for student learning outcomes. The type of research used by researchers in this research is field research with a phenomenological approach, which means that the process in the research is carried out directly by directly observing the research site through the observation method. It means the process of observing and recording is carried out systematically regarding the symptoms researched. This research was conducted at Al Azhar Islamic High School 19 Ciracas, East Jakarta. Data was collected through observation, interviews and questionnaires to both educators and students as well as by collecting data on student learning outcomes through SIDU. The results of this study indicate that the implementation of the Moodle application media in virtual learning through SIDU at SMAI Al Azhar 19 Ciracas, East Jakarta has a positive impact on student learning outcomes. It was found that the use of Moodle as a virtual learning medium was able to improve student learning outcomes in the learning process.